Anti-Warburg effect of rosmarinic acid via miR-155 in gastric cancer cells - Han S; Yang SH; Cai Z; Pan DY; Li Z; Huang ZH; Zhang PS; Zhu HJ; Lei LJ; Wang WW (Dove Medical Press, 2015)
Shuai Han,* Shaohua Yang,* Zhai Cai, Dongyue Pan, Zhou Li, Zonghai Huang, Pusheng Zhang, Huijuan Zhu, Lijun Lei, Weiwei Wang Department of General Surgery, Zhujiang Hospital, Southern Medical University, Guangzhou, People’s Republic of China *These authors contributed equally to this study Background: The Warburg effect refers to glycolytic production of adenosine triphosphate under aerobic conditions, and is a universal property of most cancer cells. Chronic inflammation is a key factor promoting the Warburg effect. This study aimed to determine whether rosmarinic acid (RA) has an anti-Warburg effect in gastric carcinoma in vitro and in vivo. The mechanism for the anti-Warburg effect was also investigated.Methods: An MTT assay was used to examine MKN45 cell growth in vitro. An enzyme-linked immunosorbent assay was used to detect proinflammatory cytokines. Real-time polymerase chain reaction was used to evaluate levels of microRNA expression in cells. Protein expression was determined by Western blotting assay. Mouse xenograft models were established using MKN45 cells to assess the anti-Warburg effect in gastric carcinoma in vivo.Results: RA suppressed glucose uptake and lactate production. It also inhibited expression of transcription factor hypoxia-inducible factor-1α, which affects the glycolytic pathway. Inflammation promoted the Warburg effect in cancer cells. As expected, RA inhibited proinflammatory cytokines and microRNAs related to inflammation, suggesting that RA may suppress the Warburg effect via an inflammatory pathway, such as that involving interleukin (IL)-6/signal transducer and activator of transcription-3 (STAT3). miR-155 was found to be an important mediator in the relationship between inflammation and tumorigenesis. We further showed that miR-155 was the target gene regulating the Warburg effect via inactivation of the IL-6/STAT3 pathway. Moreover, we found that RA suppressed the Warburg effect in vivo.Conclusion: RA might potentially be a therapeutic agent for suppressing the Warburg effect in gastric carcinoma. Keywords: rosmarinic acid, miR-155, inflammation, Warburg effect, MKN45